PROFESIONALISME APARATUR DESA SEBAGAI INSTRUMEN PENGUATAN TATA KELOLA PEMBANGUNAN PUBLIK DI DESA ILOHELUMA KECAMATAN PATILANGGIO KABUPATEN POHUWATO - Rusni Djafar; Umar Sune (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2026)
This study analyzes the professionalism of village apparatus as an instrument for strengthening public development governance in Iloheluma Village, Patilanggio District, Pohuwato Regency. The research employed a descriptive qualitative approach with a case study design involving 12 purposively selected informants, consisting of the village head, village secretary, village officials, and community figures. Data were collected through interviews, observation, and documentation, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that village apparatus professionalism has gradually developed from kinship-based work patterns toward more formal, accountable, and service-oriented governance practices. The apparatus demonstrate social responsibility, dedication, and routine coordination that support public service delivery and village development implementation. However, institutional autonomy, consistent compliance with procedures, and internalization of professional values still need strengthening. Therefore, capacity building, organizational system improvement, and consistent leadership are needed to make professionalism a sustainable foundation for public development governance in the village.